A Study on The Effect of Class of Honda Program on The Student’s Self-Efficacy in The Vocational High Schools in Yogyakarta - Ibnu Siswanto (VANOS Journal of Mechanical Engineering Education, 2021)
Vocational High Schools have to develop a good partnership with industry in order to prepare their graduates to be ready to work in certain areas of expertise, study in a higher education, or become an entrepreneur. One form of cooperation between vocational schools and industry is the special Honda class program. This program was implemented in more than 343 vocational high schools since 2015 by PT. Astra Honda Motor. It was developed as one of PT. Astra Honda Motor programs to support the development of vocational education in Indonesia. Therefore, this study aims to identify the self-efficacy of students in a special Honda class. This study used a descriptive method with a total sample of 219 from a total population of 647 students. Collecting data using a questionnaire. The results showed that the students' self-efficacy levels were high (18%) moderate (67%), and low (16%). The highest factor influencing student self-efficacy is the psychological state or student’s ability to control their emotions (4.22) and the lowest is vicarious experience or student’s belief in being able to do something based on observations of others (2.48).